A pilot randomized controlled trial to explore the feasibility of a peer-delivered single-session brief intervention for youth with moderate risk substance use - Florence Jaguga; Matthew Turissini; Edith Kamaru Kwobah; Edith Apondi; Leslie A. Enane; Julius Barasa; Gilliane Kosgei; Yvonne Olando; Mary A. Ott; Allan Kimaina; Matthew C. Aalsma (PLoS ONE, 2026)
Background Youth in sub-Saharan Africa are at high risk of substance use yet lack access to appropriate interventions. The goal of this project was to evaluate the feasibility of a definitive trial to explore efficacy of a peer-delivered single-session brief intervention (SSBI) for youth with substance use in Kenya. Methods Seventy youth aged 15−24 years with moderate risk substance use were randomized to SSBI or to psychoeducation. Data was collected at baseline and month three. Primary outcomes: Feasibility criteria, e.g., study participation rate, proportion of participants willing to be randomized, and study completion rate. Strategies for recruitment in a future trial were collected using focus group discussions with the youth at month three. Secondary outcomes: (i) Change in substance use (Alcohol, Smoking & Substance Use Involvement Screening Test for Youth [ASSIST-Y] questionnaire), depression (Patient Health Questionnaire [PHQ-9]), anxiety (Generalized Anxiety Disorder [GAD-7 scale]), and quality of life (World Health Organization-Quality of Life Brief Version [WHO-QOL BREF]) scores between baseline and month 3; (ii) Fidelity to the intervention assessed using fidelity checklists. Results This pilot met most of the predefined minimum requirements for feasibility. For instance, 96.9% of those meeting eligibility criteria consented to participate (benchmark was 80%), and 100% of those who consented were willing to be randomized to either study arm. Youth reported that young people who use substances can be most effectively recruited from community settings. The SSBI showed a small effect on reducing total ASSIST-Y (Standardized Mean Difference [SMD] −0.33 95% Confidence Interval [CI] −0.83,0.16) scores in the intervention group compared to the control. There was a moderate improvement in the quality of life for the intervention group compared to the control (SMD −0.41 CI −0.91,0.09). The intervention had no effect on depression (SMD 0.23 CI −0.27,0.72) and anxiety symptoms (SMD 0.70 CI 0.19,1.2) at month 3. Conclusion It is feasible to conduct a randomized controlled trial of a peer-delivered SSBI for youth with moderate risk substance use in Kenya. Trial registration ClinicalTrials.gov NCT05545904 Registration date: 16/09/2022, https://clinicaltrials.gov/study/NCT05545904 .